2008
DOI: 10.1016/j.enganabound.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional acoustics model using the method of fundamental solutions

Abstract: The method of fundamental solutions (MFS) is formulated in the frequency domain to model the sound wave propagation in threedimensional (3D) enclosed acoustic spaces. In this model the solution is obtained by approximation, using a linear combination of fundamental solutions for the 3D Helmholtz equation. Those solutions relate to a set of virtual sources placed over a surface placed outside the domain in order to avoid singularities. The materials coating the enclosed space surfaces can be assumed to be sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The MFS is a simple and efficient scheme and has been widely applied to various engineering and science problems, such as heat conduction [17][18][19], acoustics [20,21], diffusion-reaction [22,23], axisymmetric elasticity [24], stokes problem [25][26][27][28], and free vibration [29][30][31], just to mention a few. Furthermore, Smyrlis and Karageorghis [32][33][34][35][36], Drombosky [37], Marin [38], and Lin et al [39] presented some fundamental theoretical analysis about the MFS.…”
Section: The Methods Of Fundamental Solutionsmentioning
confidence: 99%
“…The MFS is a simple and efficient scheme and has been widely applied to various engineering and science problems, such as heat conduction [17][18][19], acoustics [20,21], diffusion-reaction [22,23], axisymmetric elasticity [24], stokes problem [25][26][27][28], and free vibration [29][30][31], just to mention a few. Furthermore, Smyrlis and Karageorghis [32][33][34][35][36], Drombosky [37], Marin [38], and Lin et al [39] presented some fundamental theoretical analysis about the MFS.…”
Section: The Methods Of Fundamental Solutionsmentioning
confidence: 99%
“…The work by António et al (2008) revealed that the accuracy of the response computed using a 3D MFS model will significantly depend on the position of the virtual sources, used to simulate the pressure field. For this reason, a preliminary study will be performed, verifying the behaviour of the method against a reference solution known for a simple geometric configuration, with the purpose of defining an adequate position for those sources and to ensure that meaningful results will be obtained.…”
Section: Model Verificationmentioning
confidence: 99%
“…In one of the few published works, António et al (2008) simulated the propagation of sound within a closed space, using a MFS formulation. In that work, the authors used a single-domain formulation and concluded that the accuracy of the method depends on the number and location of the virtual sources.…”
Section: Introductionmentioning
confidence: 99%
“…Some interesting applications of the MFS are the boundary singularity problem, 41 the eigenvalue problem, 42 room acoustics, 43,44 and underwater acoustics. 45,46 …”
Section: S Leementioning
confidence: 99%